Interest Rate Development as an Indicator of Credit Market Integration - Černohorský, Jan (My University, 2018)
The goal of this paper is to evaluate the development of credit market integration in selected European Union countries on the basis of an analysis of the development of lending and deposit interest rates. We began with the values of the nominal lending and deposit interest rates published by the International Monetary Fund. These rates are basic interest rates in each economy which are set by central banks. For this, we have used existing interest rate differentials in selected European countries calculated as the difference between the given rate in a specific country and the average of the given rate in the European Monetary Union. The selected indicators are used as a standard tool for evaluating credit market integration. We judged their relationships using the mathematical-statistical method of single-factor analysis of variance. For deposit interest rates, the degree of integration did not show any distinct changes; for lending interest rates, the degree of integration decreased slightly. We proved that the method used in this paper is able to assess not only the degree of credit market integration but also of financial markets as a whole.
Vývoj úrokové sazby jako indikátor integrace úvěrových trhů
Keywords: credit markets, integration, lending interest rate, deposit interest rate; úvěrové trhy, integrace, zápůjční úroková sazba, depozitní úroková sazba